Integrating Lipid and Starch Grain Analyses From Pottery Vessels to Explore Prehistoric Foodways in Northern Gujarat, India - García-Granero, Juan José; Suryanarayan, Akshyeta; Cubas, Miriam; Craig, Oliver E.; Cárdenas, Marc; Ajithprasad, P.; Madella, Marco (Frontiers in Ecology and Evolution, 2022)
This study attempts a holistic approach to past foodways in prehistoric northern Gujarat, India, by considering evidence of food production, distribution, preparation and consumption. We present here the results of a pilot residue study, integrating lipid and starch grain analyses, conducted on 28 ceramic vessels from three Chalcolithic/Harappan settlements (c. 3300-2000 cal. BC) in northern Gujarat (India), which are discussed in the light of previous evidence of plant and animal acquisition and preparation strategies in this region. We aim to explore how the prehistoric inhabitants of northern Gujarat transformed ingredients into meals, focusing on how different foodstuffs were processed. When assessed on their own, the lipid and compound-specific isotopic data suggest that animal fats were primarily processed in ceramic vessels, specifically non-ruminant fats. However, lipid residue analysis favours the detection of fat-rich animal products and is often unable to disentangle signatures resulting from the mixing of plant and animal products. The incorporation of starch grain analyses provides evidence for the processing of a range of plants in the vessels, such as cereals, pulses and underground storage organs. Together, the results provide a holistic perspective on foodways and a way forward in overcoming preservational and interpretational limitations.